The Meaning of Millennial Generation Text: Reception Analysis of #KidsJamanNow - Tutiasri, Ririn Puspita; Febriyanti, Syafrida Nurrachmi (Jurnal The Messenger, 2021)
The term Kids Jaman Now (Children Today) appears on various social media sites through content that represents the activities of young people in the current era. There are more than 1.6 million pieces of content on Instagram and more than 270 thousand pieces of content on YouTube which use the hashtag Kids Jaman Now . Through these contents, young people are perceived as a narcissistic, individualistic generation with a setback in moral values. This study uses reception analysis by conducting in depth interviews on a number of millennial generation informants who consume Kids Jaman Now contents to find out how they interpret the content. This study aims to show that young people who use social media are not consumers who receive messages passively; they have critical power towards the content they consume as digital natives who have better literacy than previous generations. The millennial generation has three different acceptances of this phenomenon. The first considers the content of Kids Jaman Now to represent a narcissistic, individualistic, and deteriorating moral values generation. The second considers Kids Jaman Now content as creativity for young people who entertain others and master digital communication technology.